The Effect of Using Iron on the Level of Hemoglobin and Physical Abilities in Soccer Players - Lateef, Mohammed; Salih, Rafee (Journal of Physical Education, 2020)
The research aimed at identifying the effect of using iron on the level of blood hemoglobin and physical abilities of soccer players/ Al Kurk Education. The researchers hypothesized significant statistical differences between pre and posttests in some bio – chemical and physical indicators of soccer players in favor of the posttests. The research was applied on (16) players from Al Kurk Education league. The researchers used special exercises along with iron dosages for (8) weeks with (24) training sessions including (3) training sessions per week. The results showed improvement in blood hemoglobin and physical abilities of soccer players.